Investment in Inflationary Economies - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper ;, 1996)
The paper presents a model of irreversible investment under uncertainty, where investment takes place whenever a threshold level of marginal returns is reached. The threshold depends positively on price volatility; a change from high to low inflation induces an upward capital stock adjustment. In economies that move in and out of temporary stabilizations, the observed effect is a negative inflation-investment correlation that replicates previous empirical findings, due to purely short-term dynamics. I study how this correlation is affected by the expected duration of each regime. Empirical evidence from ten inflationary economies confirms the predictions of the model.